KOLASE BERAS WARNA DALAM MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK DI RA MIFTAHUL ULUM TERPADU - Evi Maulidah; Diana Istiqomah (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
According to the WHO, 5-25% of preschool children experience developmental disorders. In fact, development is a very important aspect to pay attention to because it is related to the child's ability to carry out daily activities. RA Miftahul Ulum Terpadu implemented colored rice collage activities in an effort to improve fine motor skills in children. This research seeks to describe the planning, implementation, and evaluation of colored rice collage activities. The research approach used is descriptive-qualitative. The technique for determining informants is purposive sampling. The data collection method involves observation, in-depth interviews, and documentation. Meanwhile, data validity uses source triangulation.